2007
DOI: 10.1523/jneurosci.0091-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

A New Binding Motif for the Transcriptional Repressor REST Uncovers Large Gene Networks Devoted to Neuronal Functions

Abstract: The repressor element 1 (RE1) silencing transcription factor (REST) helps preserve the identity of nervous tissue by silencing neuronal genes in non-neural tissues. Moreover, in an epithelial model of tumorigenesis, loss of REST function is associated with loss of adhesion, suggesting the aberrant expression of REST-controlled genes encoding this property. To date, no adhesion molecules under REST control have been identified. Here, we used serial analysis of chromatin occupancy to perform genome-wide identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
263
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(279 citation statements)
references
References 40 publications
(46 reference statements)
15
263
0
1
Order By: Relevance
“…It is noteworthy that the transcriptionally responsive REST targets identified in our study differ from target genes identified by unbiased, genome-wide approaches, such as, for example, ChIP serial analysis of chromatin occupancy in a mouse kidney cell line (32), large-scale ChIP-seq in Jurkat cells (30), and ChIPon-chip in mouse neural stem cells (48) and parietal cortex tissue from postmortem Huntington disease brain (15). In the present study, of 13 target genes enriched for REST at 24 h and 48 h after ischemia, 10 overlap with targets identified in at least one other study (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…It is noteworthy that the transcriptionally responsive REST targets identified in our study differ from target genes identified by unbiased, genome-wide approaches, such as, for example, ChIP serial analysis of chromatin occupancy in a mouse kidney cell line (32), large-scale ChIP-seq in Jurkat cells (30), and ChIPon-chip in mouse neural stem cells (48) and parietal cortex tissue from postmortem Huntington disease brain (15). In the present study, of 13 target genes enriched for REST at 24 h and 48 h after ischemia, 10 overlap with targets identified in at least one other study (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…According to recent data on the genome-wide chromatin occupancy mediated by REST in non neuroendocrine cells, new target genes implicated in different cell functions remain to be found and their effects evaluated [43,44]. The multiplicity of these genes and their functional interactions make it necessary to perform comprehensive studies using gene array-based analyses of RIP-REST mice.…”
Section: Discussionmentioning
confidence: 99%
“…We now recognize that the complex biology of REST includes the potential for it to interact directly or indirectly with a broad and increasing array of transcriptional and epigenetic regulatory cofactors (including CoREST 4 ), to be alternatively spliced and differentially transported between the nucleus and cytoplasm, 5 to promote gene activation in addition to repression and long-term gene silencing, 6,7 to modify the epigenetic status of target gene loci distinct from effects on transcription, 8,9 to modulate genes not associated with the canonical RE1 motif, 10 and to exhibit high levels of integration with noncoding RNA networks that, among other things, mediate cell identity. 11 This remarkable flexibility in all aspects of REST regulation is consistent with our emerging appreciation for the decidedly context-specific effects of REST for establishing and maintaining cell identity and function.…”
Section: Introductionmentioning
confidence: 99%